Mitigating the Risks in Energy Retrofits of Residential Buildings in China - Jia, Ling (A+BE | Architecture and the Built Environment, 2021)
To speed up residential energy retrofitting in the Hot Summer and Cold Winter(HSCW) zone, the barriers to retrofitting projects need elimination. Energy retrofitting contributes to improving building quality and living comfort, but has not been accepted by the public. It stems from poor project performance in quality, time, costs, etc. The risk is an essential factor hindering such project objectives and project success. Residential energy retrofitting in China is exposed to various risks due to uncertainties regarding finance, organization, coordination, technology, etc. This thesis thus aims to deepen the understanding of risks in the whole process of residential energy retrofitting to smoothen its implementation and develop risk mitigation strategies for the HSCW climate zone of China. The thesis adopts Transaction Costs Theory (TCT) to identify the risks in the whole process of project implementation and assesses the importance of these risks in both objective and subjective aspects. Given the importance of homeowners-related risks and the key role of the government in retrofitting projects, this research develops s series of develop strategies for risk mitigation from the viewpoints of both homeowners and the government. The thesis contributes to the body of knowledge by conducting a systematic exploration of risks in retrofitting projects. In terms of the practical contributions, it does not only enable project managers to recognize the priority of project risks, but also help the government tackle these issues at its source for promotion of residential energy retrofitting.